DECLARATIVE MOOD OF IDEATIONAL THEME IN â€œEXUPERYâ€™S THE LITTLE PRINCE: A FUNCTIONAL GRAMMAR ANALYSIS - Istiqomah, Yulia (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2019)
This research entitled â€œDeclarative mood of Ideational Theme in â€œExuperyâ€™s The Little Princeâ€ (A Functional Grammar Analysis) discusses declarative mood in ideational theme in the position of clause used in novel. The purpose of this research is to analyze declarative mood and to analyze the constituents used in the novel The Little Prince. To analyze the issues, this research uses the theory of mood types: declarative mood by M.A.K Halliday and Christian Matthiessen (2004) as the grand theory while Linda Gerot dan Peter Wignell (1994) as supporting theory. The method used in this research is descriptive analysis. Data are taken from the novel The Little Prince by Antoine de Saint Exupery. After analyzing the data, it can be concluded that the all data are included into the declarative mood in this research, two data are included into constituent the nominal group as theme, and one data is included include into constituent prepositional phrase as theme in this research.